Biomass-Based Adsorbents for Removal of Dyes From Wastewater: A Review - Aragaw, Tadele Assefa; Bogale, Fekadu Mazengiaw (Frontiers in Environmental Science, 2021)
Dyes, especially azo dyes contained in wastewaters released from textile, pigment, and leather industries are entering into natural waterbodies. This results in environmental deterioration and serious health damages (for example carcinogenicity and mutagenesis) through food chains. Physiochemical, membrane processes, electrochemical technology, advanced oxidation processes, reverse osmosis, ion exchange, electrodialysis, electrolysis, and adsorption techniques are commonly used conventional treatment technologies. However, the limitations of most of these methods include the generation of toxic sludge, high operational and maintenance costs. Thus, technological advancements are in use to remediate dyes from effluents. Adsorption using the non-conventional biomass-based sorbents is the greatest attractive alternatives due to their low cost, sustainability, availability, and eco-friendly. We present and reviewed up-to-date publications on biomass-based sorbents used for dye removal. Conceptualization and synthesizing their state-of-the-art knowledge on their characteristics, experimental conditions used were also discussed. The merits and limitations of various biosorbents were also reflected. The maximum dye adsorption capacities of various biosorbents were reviewed and synthesized in the order of the biomass type (algae, agricultural, fungal, bacterial, activated carbon, yeast, and others). Surface chemistry, pH, initial dye concentration, temperature, contact time, and adsorbent dose as well as the ways of the preparations of materials affect the biosorption process. Based on the average dye adsorption capacity, those sorbents were arranged and prioritized. The best ﬁt of the adsorption isotherms (for example Freundlich and Langmuir models) and basic operating parameters on the removal dyes were retrieved. Which biomass-based adsorbents have greater potential for dye removal based on their uptake nature, cost-effectiveness, bulk availability, and mono to multilayer adsorption behavior were discussed. The basic limitations including the desorption cycles of biomass-based adsorbent preparation and operation for the implementation of this technology were forwarded.